(untitled) (Journal of Parents and Teachers, 2017)
Nowadays we can find an emotional illiteracy in our society which is the cause of many of the problems that people face. It is necessary to work not only on the cognitive learning, but also on the emotional one at schools. We propose storytelling as a tool for development and acquisition of the required emotional competencies.